Entering an era of dynamic structural biology… - Allen M. Orville (BMC Biology, 2018)
Abstract A recent paper in BMC Biology presents a general method for mix-and-inject serial crystallography, to facilitate the visualization of enzyme intermediates via time-resolved serial femtosecond crystallography (tr-SFX). They apply their method to resolve in near atomic detail the cleavage and inactivation of the antibiotic ceftriaxone by a β-lactamase enzyme from Mycobacterium tuberculosis. Their work demonstrates the general applicability of time-resolved crystallography, from which dynamic structures, at atomic resolution, can be obtained. See research article: https://bmcbiol.biomedcentral.com/articles/10.1186/s12915-018-0524-5.